Micro-expansion layer natural graphite negative electrode material and preparation method and application thereof
Through high-temperature and high-pressure intercalation and orderly heating expansion treatment, combined with interlayer expansion and surface coating technology of organic oxidizer and intercalation agent, the problems of poor rate performance and poor cycle stability of natural graphite anode materials in lithium-ion batteries are solved, and high-efficiency lithium ion diffusion and stable cycle performance are achieved.
Patent Information
- Application Number
- CN202510069224.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Natural graphite negative electrode materials have problems such as poor rate performance and poor cycle stability in lithium-ion batteries, mainly due to their small layer spacing, the slow diffusion of lithium ions and the volume expansion during lithium embedding is difficult to accommodate.
Through high-temperature and high-pressure interlayer and orderly heating expansion treatment, interlayer expansion and surface coating are performed using organic oxidizing agents and interlayer agents to form graphite with a layer spacing of 0.3358 to 0.3372 nm and amorphous carbon layer coating within 20 nm.
It realizes efficient lithium ion diffusion and stable cycling performance of the negative electrode material of lithium-ion battery, has faster charging and discharging speed and higher capacity retention rate, and can charge and discharge at a rate of 5C or above.
Smart Images

Figure CN119890266A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to negative electrode materials for lithium ion batteries, and specifically relates to a micro-expanded layer natural graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] The development of electric vehicles has led to an increasing focus on high-performance electrochemical energy storage devices. Rechargeable lithium-ion batteries (LIBs) have become the first choice for energy storage devices due to their outstanding advantages such as high energy density and conversion efficiency, long cycle life, and environmental friendliness. Natural graphite (NG) negative electrode materials have become one of the negative electrode materials for lithium-ion batteries due to their high theoretical specific capacity (372mAh / g), excellent electronic conductivity, and high charge and discharge reversibility. However, the lithium ion conductivity of the NG negative electrode itself is low, and there are problems such as poor rate performance and long-cycle stability during the charge and discharge process, and the easy generation of lithium dendrites, which limits its further application as a high-performance electrochemical energy storage material.
[0003] Compared with artificial graphite, the main reason for the poor rate performance and long cycle stability of NG is that the smaller interlayer spacing (0.3354nm) limits the rapid diffusion of lithium ions and makes it difficult to accommodate the volume expansion during the lithium insertion process. The micro-expansion layer modification method is a modification method that uses physical or chemical means to slightly expand the graphite to increase its spacing. This modification treatment can not only increase the diffusion rate of lithium ions between graphite layers, but also alleviate the volume change of the graphite negative electrode during the lithium insertion and extraction process, thereby improving its cycle stability. However, strong oxidizing inorganic acids such as H2SO4, HNO3, HClO4, and KMnO4 are often used in the current micro-expansion layer treatment process. These inorganic acids are too oxidizing, which makes the reaction degree difficult to control. On the other hand, it will cause serious equipment corrosion, impurity residues and other problems, making it difficult to industrialize production.
[0004] In addition to adjusting the graphite crystal structure, surface coating treatment can improve the electrochemical cycle stability and rapid charge and discharge performance of graphite. Its main function is to coat the active sites on the graphite surface, reduce the occurrence of irreversible side reactions, and construct a Li + Rapid diffusion of solid electrolyte interface (SEI) and the use of chemical bonding at the interface to reduce Li + Diffusion energy barrier, increasing Li + The diffusion rate in the solid phase. The currently used asphalt solid phase coating process is difficult to ensure coating uniformity, and the coating layer is too thick, which affects the rapid diffusion of lithium ions and ultimately leads to unsatisfactory electrochemical performance. Therefore, it is necessary to improve the surface coating process of graphite and develop a process technology with thin and uniform surface coating to improve the electrochemical performance of graphite. Summary of the invention
[0005] In view of the problems existing in the current natural graphite negative electrode materials, the present invention provides a micro-expanded layer natural graphite negative electrode material, which solves the problems of poor rate performance and poor cycle stability caused by volume expansion faced by natural graphite through the modification of interlayer expansion and surface coating of natural graphite.
[0006] The oxidant and intercalant used are both organic, with mild reaction, strong controllability of interlayer structure, and complete decomposition after carbonization without residual impurities. The high temperature and high pressure intercalation adopted can ensure the uniformity of intercalation structure while avoiding the generation of a large amount of wastewater. The spray coating method adopted can achieve uniform and dense coating layer and improve the surface state of natural graphite. The prepared natural graphite negative electrode material has faster charge and discharge speed and more stable cycle performance, and its process steps are simple and efficient.
[0007] The technical solution of this application is as follows:
[0008] In a first aspect, the present application provides a micro-expanded layer natural graphite negative electrode material, wherein the negative electrode material comprises graphite with an interlayer spacing of 0.3358 to 0.3372 nm and an amorphous carbon layer within 20 nm wrapped on the graphite.
[0009] Through the modification of interlayer expansion and surface coating of natural graphite, the problems of poor rate performance and poor cycle stability caused by volume expansion faced by natural graphite are solved. As the negative electrode material of lithium-ion batteries, the reversible capacity of micro-expanded natural graphite can reach 388mAh / g, the first efficiency is greater than 93%, and the capacity retention rate is above 80% after 2000 cycles. At the same time, the natural graphite negative electrode can be charged and discharged at a rate of more than 5C.
[0010] As a specific implementation of the present application, the graphite is natural graphite;
[0011] Preferably, the natural graphite includes at least one of flake graphite, spherical graphite and microcrystalline graphite.
[0012] In a second aspect, the present application provides a method for preparing the above-mentioned micro-expanded layer natural graphite negative electrode material, comprising the following steps:
[0013] (1) High temperature and high pressure intercalation: natural graphite powder is mixed with an intercalation agent and an oxidant and treated under high temperature and high pressure;
[0014] (2) Orderly heating and layer expansion: the natural graphite powder of step (1) is heated in an orderly manner under the protection of an inert gas;
[0015] (3) Polymer coating: dissolving the polymer in a solution, pouring the natural graphite powder of step (2), stirring to prepare a slurry, and drying;
[0016] (4) High temperature carbonization: The material of step (3) is treated at high temperature under the protection of an inert gas to obtain a micro-expanded layer natural graphite negative electrode material.
[0017] As a specific implementation of the present application, the intercalant in step (1) includes an organic acid; preferably, the organic acid includes at least one of formic acid, acetic acid, oxalic acid, propionic acid, and butyric acid.
[0018] As a specific implementation of the present application, the oxidant includes hydrogen peroxide.
[0019] As a specific implementation of the present application, the mass ratio of the natural graphite powder to the intercalant in the step (1) is 1: (0.2-2): (0.5-2).
[0020] As a specific implementation of the present application, the conditions for the high temperature and high pressure treatment in step (1) include: a temperature of 60 to 150° C. and a time of 1 to 10 hours.
[0021] As a specific embodiment of the present application, the conditions for the orderly heating in step (2) include: heating to 200-300°C at 0.5-1°C / min for 0.5-1h, and then heating to 350-450°C at 1-2°C / min for 0.5-2h.
[0022] As a specific embodiment of the present application, the polymer in step (3) includes at least one of phenolic resin, urea-formaldehyde resin, benzoxazine resin, polyacrylonitrile resin, coal tar, and petroleum asphalt;
[0023] As a specific embodiment of the present application, the solvent described in step (3) includes water or an organic solvent;
[0024] As a specific embodiment of the present application, the drying described in step (3) includes spray drying.
[0025] As a specific implementation of the present application, the mass ratio of the natural graphite powder to the polymer in step (3) is 100:2-10.
[0026] As a specific implementation of the present application, the high temperature treatment conditions in step (4) include: heating temperature 1000-1300° C., heating time 1-6 hours.
[0027] In a third aspect, the present application provides the use of the above-mentioned micro-expanded layer natural graphite negative electrode material or the micro-expanded layer natural graphite negative electrode material prepared by the above-mentioned method in lithium-ion batteries.
[0028] Beneficial effects of the present invention
[0029] (1) The effective control of the graphite interlayer spacing between 0.3358 and 0.3372 nm is achieved through high temperature and high pressure intercalation and orderly heating and expansion. The oxidant and intercalation agent used are both organic matter, the reaction conditions are mild, the process is controllable, and after heating treatment, they are completely decomposed without residue. High temperature and high pressure intercalation can save water and avoid the generation of wastewater, and can also promote the uniform insertion of the intercalation agent into the graphite interlayer to form interlayer compounds. Orderly heating and expansion adopts the method of slow heating and step-by-step heating to achieve the orderly decomposition of the intercalation agent, thereby effectively controlling the size of the graphite interlayer spacing and avoiding the phenomenon of graphite exfoliation caused by excessive decomposition reaction.
[0030] (2) Spray drying can achieve uniform coating of the polymer on the surface of graphite particles, and the coating thickness is controlled within 20 nm, avoiding the phenomenon of graphite flakes being peeled off during conventional high-speed mixing, and the coating layer is thinner and more uniform.
[0031] (3) Excellent electrochemical performance: As a negative electrode material for lithium-ion batteries, the reversible capacity of micro-expanded natural graphite can reach 388mAh / g, the initial efficiency is greater than 93%, and after 2,000 cycles, the capacity retention rate is above 80%. At the same time, the natural graphite negative electrode can be charged and discharged at a rate of more than 5C.
[0032] (4) The synthesis process of the present invention is simple, easy to control, safe and reliable, has low production cost and high yield, and is suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 This is a scanning electron microscope image of the sample of Example 1;
[0035] Figure 2 is the XRD pattern of the sample of Example 1;
[0036] Figure 3 The first charge and discharge diagram of Example 1 and Comparative Example 1 as negative electrodes of lithium-ion batteries;
[0037] Figure 4 This is a cycle performance diagram of Example 1 as a negative electrode of a lithium ion battery. DETAILED DESCRIPTION
[0038] Example 1
[0039] A method for preparing a micro-expanded layer natural graphite negative electrode material comprises the following steps:
[0040] (1) High temperature and high pressure intercalation: Natural graphite powder is mixed with formic acid (intercalation agent) and hydrogen peroxide (oxidant) at a mass ratio of 1:0.5:1 under high-speed stirring, and then transferred to a high-pressure reactor and heated to 80°C for 2 hours.
[0041] (2) Orderly heating and layer expansion: After washing and drying, the natural graphite powder of step (1) is placed in a heating furnace, and heated at 1°C / min to 250°C for 0.5h under the protection of inert gas, and then heated at 2°C / min to 400°C for 1h;
[0042] (3) Polymer spray coating: dissolve phenolic resin in aqueous solution, pour in natural graphite powder of step (2), the mass ratio of natural graphite to phenolic resin is 100:5, stir to prepare slurry, and after spray drying, the surface of graphite particles is evenly coated with phenolic resin material.
[0043] (4) High-temperature carbonization: The material of step (3) is placed in a high-temperature furnace, heated to 1200° C. for 4 h under the protection of an inert gas, and a carbon-coated natural graphite material is obtained.
[0044] Figure 1 The transmission electron microscopy results show that the surface of natural graphite is covered with an amorphous carbon layer, which is uniform and dense with a thickness of about 12nm. Figure 2 The XRD pattern of Example 1 shows that the interlayer spacing is significantly increased, and the interlayer spacing is calculated to be 0.3365nm. The electrochemical results show that Figure 3 , Figure 4 The first charge and discharge efficiency of the surface-modified silicon-carbon material is 93.4%, the first charge specific capacity is 388 mAh / g, and after 1,000 cycles, the capacity retention rate is 88%, and the cycle performance is stable.
[0045] Example 2
[0046] A method for preparing a micro-expanded layer natural graphite negative electrode material comprises the following steps:
[0047] (1) High temperature and high pressure intercalation: Natural graphite powder is mixed with acetic acid (intercalation agent) and hydrogen peroxide (oxidant) in a mass ratio of 1:2:2 under high-speed stirring, and then transferred to a high-pressure reactor and heated to 60°C for 10 hours.
[0048] (2) Orderly heating and layer expansion: After washing and drying, the natural graphite powder of step (1) is placed in a heating furnace, and heated at 0.5°C / min to 200°C for 1 h under the protection of inert gas, and then heated at 1°C / min to 350°C for 2 h;
[0049] (3) Polymer spray coating: dissolve the benzoxazine resin in an acetone solution, pour in the natural graphite powder of step (2), the mass ratio of natural graphite to benzoxazine resin is 100:10, stir to prepare a slurry, and after spray drying, the surface of the graphite particles is evenly coated with the benzoxazine resin material.
[0050] (4) High-temperature carbonization: The material of step (3) is placed in a high-temperature furnace, heated to 1300° C. for 1 h under the protection of an inert gas, and a carbon-coated natural graphite material is obtained.
[0051] Example 3
[0052] A method for preparing a micro-expanded layer natural graphite negative electrode material comprises the following steps:
[0053] (1) High temperature and high pressure intercalation: Natural graphite powder is mixed with oxalic acid (intercalation agent) and hydrogen peroxide (oxidant) at a mass ratio of 1:0.2:0.5 by high-speed stirring, and then transferred to a high-pressure reactor and heated to 150°C for 1 hour.
[0054] (2) Orderly heating and layer expansion: After washing and drying, the natural graphite powder of step (1) is placed in a heating furnace, and heated at 1°C / min to 300°C for 1 h under the protection of inert gas, and then heated at 2°C / min to 450°C for 0.5 h;
[0055] (3) Polymer spray coating: Dissolve polyacrylonitrile resin in N,N-dimethylformamide solution, pour in the natural graphite powder of step (2), the mass ratio of natural graphite to polyacrylonitrile resin is 100:2, stir to prepare a slurry, and after spray drying, the surface of the graphite particles is evenly coated with polyacrylonitrile material.
[0056] (4) High-temperature carbonization: The material of step (3) is placed in a high-temperature furnace, heated to 1000° C. for 6 h under the protection of an inert gas, and a carbon-coated natural graphite material is obtained.
[0057] Example 4
[0058] A method for preparing a micro-expanded layer natural graphite negative electrode material comprises the following steps:
[0059] (1) High temperature and high pressure intercalation: Natural graphite powder is mixed with butyric acid (intercalation agent) and hydrogen peroxide (oxidant) in a mass ratio of 1:1:2 under high-speed stirring, and then transferred to a high-pressure reactor and heated to 120°C for 5 hours.
[0060] (2) Orderly heating and layer expansion: After washing and drying, the natural graphite powder of step (1) is placed in a heating furnace, and heated at 1°C / min to 250°C for 1 h under the protection of inert gas, and then heated at 2°C / min to 450°C for 1 h;
[0061] (3) Polymer spray coating: dissolve petroleum asphalt in tetrahydrofuran solution, pour in the natural graphite powder of step (2), the mass ratio of natural graphite to petroleum asphalt is 100:7, stir to prepare a slurry, and after spray drying, the surface of the graphite particles is evenly coated with asphalt material.
[0062] (4) High-temperature carbonization: The material of step (3) is placed in a high-temperature furnace, heated to 1100° C. for 6 h under the protection of an inert gas, and a carbon-coated natural graphite material is obtained.
[0063] Comparative Example 1-No micro-expansion treatment
[0064] Compared with Example 1, steps (1) and (2) are omitted, and the rest are the same as Example 1.
[0065] Comparative Example 2-Asphalt Solid Phase Coating
[0066] Compared with Example 1, step (3) is to crush the high-temperature asphalt and mix it with natural graphite powder in a mass ratio of 5:100 to obtain a mixed powder, and the rest is the same as Example 1.
[0067] Comparative Example 3 - Microwave Heating Layer Expansion
[0068] Compared with Example 1, step (2) does not adopt sequential heating treatment, but instead performs microwave heating treatment on the graphite powder. The rest is the same as Example 1.
[0069] Implementation effect example
[0070] The micro-expanded natural graphite prepared in Examples 1-4 and Comparative Examples 1-3 was used as the negative electrode material of lithium-ion batteries to compare the electrochemical performance. The specific experimental process was as follows: the micro-expanded natural graphite material prepared in Examples 1-4 and Comparative Examples 1-3: conductive carbonization: CMC binder = 93:2:5; lithium sheet was used as the counter electrode and reference electrode; the electrolyte was 1M LiPF6-EC / DMC (volume ratio 1:1), and the charge and discharge rate was 0.1C. The experimental results are shown in Table 1.
[0071] Table 1 Comparison of electrochemical properties of negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-3
[0072]
[0073] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A micro-expanded layer natural graphite negative electrode material, characterized in that: The negative electrode material comprises graphite with an interlayer spacing of 0.3358 to 0.3372 nm and an amorphous carbon layer within 20 nm wrapped on the graphite.
2. The micro-expanded layer natural graphite negative electrode material according to claim 1, characterized in that: The graphite is natural graphite; Preferably, the natural graphite includes at least one of flake graphite, spherical graphite and microcrystalline graphite.
3. A method for preparing the micro-expanded layer natural graphite negative electrode material according to claim 1 or 2, characterized in that: The following steps are involved: (1) High temperature and high pressure intercalation: natural graphite powder is mixed with an intercalation agent and an oxidant and treated under high temperature and high pressure; (2) Orderly heating and layer expansion: the natural graphite powder of step (1) is heated in an orderly manner under the protection of an inert gas; (3) Polymer coating: dissolving the polymer in a solution, pouring the natural graphite powder of step (2), stirring to prepare a slurry, and drying; (4) High temperature carbonization: The material of step (3) is treated at high temperature under the protection of an inert gas to obtain a micro-expanded layer natural graphite negative electrode material.
4. The preparation method according to claim 3, characterized in that: The intercalant in step (1) comprises an organic acid; preferably, the organic acid comprises at least one of formic acid, acetic acid, oxalic acid, propionic acid and butyric acid; And / or, the oxidant comprises hydrogen peroxide.
5. The preparation method according to claim 3, characterized in that: The mass ratio of the natural graphite powder to the intercalant in step (1) is 1: (0.2-2): (0.5-2); And / or, the conditions for treatment under high temperature and high pressure include: temperature of 60 to 150° C. and time of 1 to 10 hours.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The conditions for the sequential heating in step (2) include: heating to 200-300°C at a rate of 0.5-1°C / min for 0.5-1h, and then heating to 350-450°C at a rate of 1-2°C / min for 0.5-2h.
7. The preparation method according to any one of claims 3 to 5, characterized in that: The polymer in step (3) comprises at least one of phenolic resin, urea-formaldehyde resin, benzoxazine resin, polyacrylonitrile resin, coal tar, and petroleum asphalt; and / or, the solvent comprises water or an organic solvent; And / or, the drying comprises spray drying.
8. The preparation method according to any one of claims 3 to 5, characterized in that: The mass ratio of the natural graphite powder to the polymer in step (3) is 100:2-10.
9. The preparation method according to any one of claims 3 to 5, characterized in that: The high temperature treatment conditions in step (4) include: heating temperature 1000-1300° C., heating time 1-6 hours.
10. Use of the micro-expanded layer natural graphite negative electrode material according to claim 1 or 2 or the micro-expanded layer natural graphite negative electrode material prepared by the method according to any one of claims 3 to 9 in lithium ion batteries.